TRAINING EFFECT CONTRIBUTE TO THE JOB SATISFACTION AND PERFORMANCE OF CIVIL SERVICE IN THE TRANSMIGRATION AND MANPOWER SERVICE OF BULUNGAN REGENCY - Sumarni Sumarni; Ana Sriekaningsih; Milwan Milwan (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2021)
The rationale of this study was to analyze and prove the training effect on the performance of the Civil Service through job satisfaction variables. Type of research is included in explanatory research. The population is all employees of Transmigration and Manpower Office of Bulungan Regency about 55 persons. The number of samples in this study were 55 respondents. The sampling technique performed by using total sampling technique. Data analysis technique used a path analysis approach. The findings showed that training has a positive and significant effect on employee job satisfaction. Training has a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance. In step 1, training is proven to have a significant effect on employee performance. In step 2 when training and job satisfaction are regressed together to predict employee performance, training remains significant. Thus job satisfaction is able to mediate the effect of training on employee performance.